A política cultural do Conselho Federal de Cultura, 1966-1976 - Costa, Lílian Araripe Lustosa da (2011)
The Federal Council of Culture, created in 1966, was inspired on the Federal Council of Education, being strictly linked to the Ministry of Education and Culture. This council was advisory and informative, compound by several renowned intellectuals, both national and international, mainly from Brazilian Academy of Letters and from the Brazilian Historic and Geographic Institute. From 1966 to 1976 the council had the most concentrated activities, so this is the period chosen for the analysis in this work. We investigated herein how the cultural politic was intended, and in a certain way implemented by the council, through three main projects: the National Plan of Culture elaboration, the State Councils of Culture implantation and the Culture House. For a deepening of those questions will be realized a case study of the Culture Secretary of the Ceará State founding, the first one in the country, as its respective State Council, created in 1966, previously to the Federal Council of Culture.